Potential Implementation Of Sharia Business Contract In The World Of Islamic Boarding Schools - Muhammad Zuhirsyan (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to look at the implementation of the application of the empowerment of Islamic banking business contracts in Islamic boarding schools. The study was conducted at several pesantren in the North Sumatra region. This study uses a qualitative phenomenological approach that is descriptive analytical and inductive. Data collection methods in the study used observations and interviews with various related parties. The type of data used in this study is primary and secondary data. Analysis of the data used is descriptive by using literature studies in the form of muamalah fiqh books. The results showed that the application of business contracts in boarding schools is still rarely applied. Some of the potential for this application can be realized both in the field of education and business sectors carried out by the pesantren.